2020
DOI: 10.1021/jacs.0c02522
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of (−)-Spirochensilide A

Abstract: An asymmetric total synthesis of (−)-spirochensilide A has been achieved for the first time. The synthesis features a semipinacol rearrangement reaction to stereoselectively construct the two-vicinal quaternary chiral centers at C8 and C10, a tungsten-mediated cyclopropene-based Pauson–Khand reaction to install the C13 quaternary chiral center, and a furan-based oxidative cyclization to stereoselectively form the spiroketal motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 74 publications
2
44
0
Order By: Relevance
“…In 2020, Chen and Yang's group proposed an elegant total synthesis of (−)-spirochensilide A. 24 During their early-stage synthesis, a two-step epoxidation/semipinacol ring-contraction consequence has been developed to convert a trans -octahydronaphthalene system 15 to an octahydroindene carbocycle 17 with vicinal quaternary carbon centers ( Scheme 5 ). Of note, only a single diastereoisomer was obtained in the rearrangement reaction of 16 , indicating a highly regio- and diastereochemical control of the ring-contraction process, and the aldehyde functionality introduced through the rearrangement could be further elaborated as a functional handle.…”
Section: Epoxidesmentioning
confidence: 99%
“…In 2020, Chen and Yang's group proposed an elegant total synthesis of (−)-spirochensilide A. 24 During their early-stage synthesis, a two-step epoxidation/semipinacol ring-contraction consequence has been developed to convert a trans -octahydronaphthalene system 15 to an octahydroindene carbocycle 17 with vicinal quaternary carbon centers ( Scheme 5 ). Of note, only a single diastereoisomer was obtained in the rearrangement reaction of 16 , indicating a highly regio- and diastereochemical control of the ring-contraction process, and the aldehyde functionality introduced through the rearrangement could be further elaborated as a functional handle.…”
Section: Epoxidesmentioning
confidence: 99%
“…[62] Yang and coworkers demonstrated the first stereoselective total synthesis of (À )-spirochensilide A (Scheme 21). [63] This synthesis incorporates semipinacol rearrangement, tungstenassisted cyclopropene-centered Pauson-Khand reaction, and oxidative ring formation reaction of furan to build the spiroketal entity, stereoselectively.…”
Section: (à )-Sinularianin B (14)mentioning
confidence: 99%
“…Higher base loading causes a faster reaction and lower enantioselectivity (Scheme 52). [114] During the investigation of ring-opening annulation reaction Matsuda et al found that base mediated ring-opening annulation of cyclopropenone and carbonyl or ester is extensively studied but the same reaction with amide or aldehyde remains unexplored. They developed a silver triflate catalyzed ring-opening [3 + 2] annulation reaction of 258 and 259 to give 260 in good yield.…”
Section: Miscellaneousmentioning
confidence: 99%